Conveying The Negative Health Consequences of Smoking For The Development of School-Based Social Marketing Programs: An Experimental Study - Mohammad Eko Fitrianto; Basu Swastha Dharmmesta; Bernardinus Maria Purwanto (SRIWIJAYA INTERNATIONAL JOURNAL OF DYNAMIC ECONOMICS AND BUSINESS, 2023)
Cigarette products certainly have a negative impact on health, especially for teenagers. Although there is a growing body of literature on the positive social influence of peers as a preventative measure, it is unclear how they react when convinced of the truth of its negative impact on health. This experimental study aims to examine the impact of negative health consequences on adolescents' emotions and behavior. Through an online invitation and randomization process, 78 high school students from South Sumatra Province, Indonesia were eligible to participate in the online experimental study. We compared two groups (experimental vs. control) to examine the impact of negative health consequences on their emotions (empathy) and behavior (prosocial behavior). Our findings show that, as compared to adolescents in the non-convincing health message condition (n=40), adolescents in the convincing negative health message condition (n=38) had higher empathy (sign=0.005) and prosocial behavior (sign=0.028) to assist their smoking peers. Our findings provide a valuable information to sustainability development in the future through reducing underage smokers. We suggest that the use of convincing method to develop a school-based social marketing program for handling adolescent smoking problem